Facilitator roles of viruses in enhanced insect resistance to biotic stress - Jagdale, Shounak S.; Joshi, Rakesh S. (Current Opinion in Insect Science, 2019)
Virus-insect interactions are primarily parasitic, yet diverse mutualistic interactions, some of which are symbiogenic, also occur. These viruses can modify insect physiology and behavior so that hosts can gain resistance against various biotic challenges like pathogen and parasites. In the recent past, many insect mutualistic viruses have been reported. Viruses can show symbiogenic interactions with some insects, which have been explored at the molecular level. However, understanding about molecular mechanisms for many of the mutualistic viruses is still enigmatic. Exploration of these interactions and its mechanism can shed light on phenomenon of virus mediated biotic stress resistance in insects.